Factors Affecting Investment Decisions of Employees Working on Financial and Non-Financial Sectors: A Case of Pokhara Metropolitan City, Nepal - Chapagain, Ramkrishna; Dhungana, Bharat Ram; Karmacharya, Bibek (Journal of Nepalese Business Studies, 2022)
The emergence of the financial market favorably influences the economy. The choices of an individual engaging in the financial market have a crucial part in setting the market trend, which subsequently affects the economy. This research seeks to examine the variables impacting the investment choices of people functioning in financial and non-financial sectors. The research employs a social survey design, based on 280 samples obtained by a structured questionnaire employing a convenience sampling approach. The study was restricted to the Pokhara metropolitan city of Nepal. Descriptive Statistics, Chi-square test, t-test, ANOVAs, Confirmatory Factor Analysis and Structural Equation Modeling were utilized to fulfill the study goals. The study demonstrates that there is no substantial difference between personnel working in the financial and non-finance industries on herding, market, heuristic and demographic component. However, people working in the financial industry examine more economic aspects and the total investment performance is greater for employees working in the financial sector. Further, the research reveals that self-confidence, market information, the recommendation of professionals, minimization through portfolio diversification and high-income level increases in interest in investment were the significant influential factors affecting investment decisions of an employee working in financial and non-financial institutions. The CFA establishes a significant link between observable variables and their fundamental constructs. The path analysis demonstrates that Market, Herding, Knowledge and Economic factors has a favorable influence on investment choices. The regulatory authority and related institutions should equip investors in respect of both economic and behavioral elements to make a smart investment choice.